Penerapan Konvensi ILO pada Industri Garmen Bangladesh (Studi Kasus: Diskriminasi Pekerja Garmen Perempuan) - Apsari, Ratih Dinda; Yuniati, Sri; Indriastuti, Suyani (University of Jember, 2022)
This research begins with the problem of implementation obstacles of ILO Conventions related to discrimination in occupation and employment in the Bangladeshi garment industry. In that regards, this study aims to question What are the obstacles to implementing the ILO Conventions on Discrimination in Occupation and Employment in Bangladesh. This paper addresses this question through qualitative method by exploring secondary data. Furthermore, the data then being analyzed using qualitative descriptive analysis techniques. The results of the study indicate that implementation of ILO Conventions related to occupational and occupational discrimination has encountered obstacles in Bangladesh. These obstacles are caused by The Bangladesh Labor Act does not explain in detail about garment workers, weak oversight of the implementation of the Bangladesh Labor Act on garment companies, garment companies do not fully support the Bangladesh Labor Act, and the political conditions in Bangladesh.